Knowledge, behaviour and attitudes of Greek health care personnel regarding mobile phone use and road accidents: the 'Enigma' project. (7th October 2012) - Gerakopoulou, P; Matsoukis, I; Giagou, N; Sotiraki, M; Kousoulis, A; Bouka, E; Alexopoulos, A; Cassimos, D; Petridou, E
Abstract : Background: Mobile Phone (MP) use constitutes an established risk for road traffic accidents; there still a scientific controversy, however, on other health risks related with electromagnetic fields (EMF) emitted by MP, frequently generating high risk perceptions of the public at large. Aims: Health Care Personnel (HCP) are central figures in shaping public behaviour on sensitive health issues; we sought to 1.examine their knowledge, behaviour and attitudes regarding perceived health risks specifically related to MP use and to explore whether the discrepancy between excessive concerns on the non-established risks due to EMF emissions versus minimal concerns on evident risks due to MP use on the road also hold for HCP. Methods: In the context of ENIGMA (http://www.enigma-program.gr), an EMF-related risks information programme, 722 HCP from several Greek cities completed a 22-item structured questionnaire; data were analysed with multiple regression techniques. This quantitative approach was complemented by a double-phased qualitative method, entailing 18 semi-structured individual interviews and 3 focus groups with paediatricians, followed by an interpretive phenomenological analysis. Results: Correct knowledge about MP health risks reached a minimum 8%, whereas perceived knowledge peaked to >75%, leading to a limited accuracy of <20%. Paediatricians' excessive concerns clustered around three main themes, notably personal involvement, perceived confusion and perceptions about conflict of interest in health risk research, expressed through social conspiracy theories. Significance: Counselling by experts in sensitive issues is not always in line with evidence based scientific findings, but rather distillates from personal cognition/attitudes/characteristics suggesting a principal risk governance issue for health education policies.